2005
DOI: 10.1016/j.ejvs.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prevalence of APC-resistance in Vascular Patients and in a Normal Population Cohort in Western Germany

Abstract: Previously published increased prevalence rates of APC-R in patients with arterial disorders could not be confirmed in this study. A firm association between the presence of APC-R and previous bypass occlusion or postoperative failure of the vascular reconstruction could not be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We revealed an increased APC sensitivity in young women with a history of MI compared with controls. Previous studies on APC resistance in relation to arterial thrombosis provided contradictory results, with some studies showing an increased APC resistance in patients with arterial thrombosis and in other studies no effect of APC resistance on arterial thrombosis [21–23]. A possible explanation for the differences found in the literature may lie in differences in patient selection criteria and assays used to determine APC resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We revealed an increased APC sensitivity in young women with a history of MI compared with controls. Previous studies on APC resistance in relation to arterial thrombosis provided contradictory results, with some studies showing an increased APC resistance in patients with arterial thrombosis and in other studies no effect of APC resistance on arterial thrombosis [21–23]. A possible explanation for the differences found in the literature may lie in differences in patient selection criteria and assays used to determine APC resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the differences found in the literature may lie in differences in patient selection criteria and assays used to determine APC resistance. In the present study, APC resistance was measured using a thrombin generation‐based test rather than an APTT‐based test [21,24]. These assays have different determinants: the CAT test is primarily dependent on free TFPI and protein S, whereas the APTT‐based test is mainly determined by FVIII levels [12,25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sampram and Lindblat 24 suggested that an FVL mutation was associated with a doubled rate of failure for infrainguinal procedures both at one month and one year (37 versus 22% and 46 versus 27%). In contrast, Evans et al 25 only reported one APC resistant patient in 116 claudicants, while Aleksić et al 26 showed neither an increased prevalence of APCR in patients with PAOD nor a firm association between the presence of APCR and previous bypass occlusion or postoperative failure of the vascular reconstruction. Variations in reported figures and even opposing findings of various studies may be explained by the preferential use of DNA analysis or APC ratio to define FVL; variations in the lower value of the normal range for defining the normal APC ratio; and the severity of the presenting PAOD.…”
Section: Discussionmentioning
confidence: 95%
“…17 But in contrast to a solid association between FVL and venous thrombosis, the data relating FVL and arterial events remain controversial. Nevertheless, some clinical studies suggest an increased risk of thrombosis after arterial revascularization, [18][19][20][21][22][23][24][25] implicating vessel wall injury during the revascularization procedure as the triggering event. Not unexpectedly, the relationship between FVL and failure of arterial reconstructive procedures appears especially high in homozygotes.…”
Section: Discussionmentioning
confidence: 99%